Performance of Cement Mortar Exposed to Different Temperature and Curing Methods - Samer Muayad Alsadik; Esraa Lutfi Ibrahim; Hussein Ali Jaber (Salehan Institute of Higher Education, 2020)
Curing is an important process to achieve the specified concrete strength and durability. The objectives here is to determine the effect of four curing regimes on the development of mechanical properties for mortar specimens with mix proportions of 1:2.75 cement to sand by mass with W/C of 0.46, and with standard cube and prism dimensions, using OPC and SRPC; specimens tested under curing temperatures at 25 °C and 45 °C; to simulate the seasonal climatic conditions in Iraq. Curing methods adopted were: 1st: immersion in water, 2nd: wetting by using saturated covers, 3rd: curing by using wax-based compound, and 4th: by air curing. The specimens were examined at the ages of 3, 7, 14, and 28 days for density and mechanical properties. The study highlights that fully-saturated specimens in water is the recommended curing; as test results indicate that the highest mechanical properties were obtained. Considering the compressive strength as the criterion, curing by using wax-based compound came 2nd; and curing by saturated covers in 3rd position. This is true for temperatures at 25 °C and 45 °C; however, the experiments carried on OPC mortar show that increasing the temperature from 25 °C to 45 °C increases the early strength at 3 and 7 days by 16% and 22%, respectively; while the strengths at 14 and 28 days indicate an opposite manner; as the strength decreases when comparing the testing results at those ages by 23% and 17%. This is also valid for SRPC mortar and water-immersion curing for the same temperatures and corresponding ages; 25% and 19% increase at 3 and 7 days, respectively; but the results show that there was a continuous increase in strength at 14 and 28 days, by 29% and 33%, respectively. The study points out that immersion-curing in high temperatures is not recommended for OPC mortars after the age of 7 days; while it could be used for SRPC mortars.